2018
DOI: 10.3126/jnps.v38i3.23477
|View full text |Cite
|
Sign up to set email alerts
|

Study of Congenital Anomalies of the Kidneys and Urinary Tract in Neonates

Abstract: Introduction: Congenital anomalies of the kidneys and urinary tract (CAKUT) comprise various structural malformations that result from defects in morphogenesis of the kidney and/or urinary tract. In most cases, CAKUT are associated with infant mortality and morbidity in older children and adults. Hence this study was undertaken to follow up antenatally diagnosed cases of CAKUT and see their outcome in the first six months of life. Material and Methods: An observational follow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Chaara et al found that multicystic dysplastic kidney (MCDK) was the most common fetal abnormality, followed by PUV, renal agenesis, and others [ 8 ]. Chougule et al observed that CAKUT were more prevalent in males, with hydronephrosis being the most frequent CAKUT detected prenatally [ 9 ]. They also noted that a significant percentage of mild hydronephrosis cases resolved postnatally within a few days, and a notable portion resolved within six months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Chaara et al found that multicystic dysplastic kidney (MCDK) was the most common fetal abnormality, followed by PUV, renal agenesis, and others [ 8 ]. Chougule et al observed that CAKUT were more prevalent in males, with hydronephrosis being the most frequent CAKUT detected prenatally [ 9 ]. They also noted that a significant percentage of mild hydronephrosis cases resolved postnatally within a few days, and a notable portion resolved within six months of age.…”
Section: Discussionmentioning
confidence: 99%